Enhancing the yield of Xenocoumacin 1 in Xenorhabdus nematophila YL001 by optimizing the fermentation process - Yunfei Han; Shujing Zhang; Yang Wang; Jiangtao Gao; Jinhua Han; Zhiqiang Yan; Yongquan Ta; Yonghong Wang (Scientific Reports, 2024)
Abstract Xenocoumacin 1 (Xcn 1), antibiotic discovered from secondary metabolites of Xenorhabdus nematophila, had the potential to develop into a new pesticide due to its excellent activity against bacteria, oomycetes and fungi. However, the current low yield of Xcn1 limits its development and utilization. To improve the yield of Xcn1, response surface methodology was used to determine the optimal composition of fermentation medium and one factor at a time approach was utilized to optimize the fermentation process. The optimal medium composed of in g/L: proteose peptone 20.8; maltose 12.74; K2HPO4 3.77. The optimal fermentation conditions were that 25 °C, initial pH 7.0, inoculum size 10%, culture medium 75 mL in a 250 mL shake flask with an agitation rate of 150 rpm for 48 h. Xenorhabdus nematophila YL001 was produced the highest Xcn1 yield (173.99 mg/L) when arginine was added to the broth with 3 mmol/L at the 12th h. Compared with Tryptic Soy Broth medium, the optimized fermentation process resulted in a 243.38% increase in Xcn1 production. The obtained results confirmed that optimizing fermentation technology led to an increase in Xcn1 yield. This work would be helpful for efficient Xcn1 production and lay a foundation for its industrial production.